Formulation and Evaluation of Antibacterial and Anti-Inflammatory Capsules Containing Phyllanthus emblica L. Fruit Nanoparticles - Masfria; Sumaiyah; Hafid Syahputra; Marwin Witarman (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Phyllanthus emblica fruit has diuretic, antibacterial, hepatoprotective, antitumor, hypocholesterolemic, antioxidant, and antiulcerogenic activities making it possible as a traditional medicine in capsule form. Capsule preparations have the advantage of covering the unpleasant taste and smell of medicinal ingredients, easy to swallow, so they are practical to use. This study aimed to formulate Phyllanthus emblica fruit nanoparticles in capsules and to test the antibacterial activity against Streptococcus mutans and Pseudomonas aeruginosa and anti-inflammatory activity by observing denaturation inhibition in vitro. The method used to manufacture Phyllanthus emblica fruit simplicia nanoparticles was used using a High Energy Ball mill grinding machine. Capsule formulation was carried out with various doses of nanoparticles (100, 150, and 200 mg). Evaluation includes weight uniformity and disintegration time. Test of its antibacterial activity against Streptococcus mutans and Pseudomonas aeruginosa and its anti inflammatory activity in vitro. The study found that all formulas could be made into capsules that met the evaluation test requirements. The results of the evaluation of disintegration time ranged from 6.17-11.33 minutes. For the evaluation results of weight uniformity, it was found that weight deviations in columns A1 and A2 were in the range between 0.9% to 2.8% and 0.9 to 1.3%. The study reports on the antibacterial activity of Phyllanthus emblica fruit nanoparticle capsules (PFNP) against Streptococcus mutans and Pseudomonas aeruginosa. The results indicate that PFNP exhibits a dose-dependent antibacterial effect, with inhibition zone diameters of 10.83 mm, 11.6 mm, and 12.63 mm observed at 100 mg, 150 mg, and 200 mg, respectively, against Streptococcus mutans. Similarly, PFNP demonstrated a dose-dependent antibacterial effect against Pseudomonas aeruginosa, with inhibition zone diameters of 10.7 mm, 11.4 mm, and 12.1 mm observed at doses of 100 mg, 150 mg, and 200 mg, respectively. PFNP capsules showed inhibition results with a value of 5.63%, 6.13%, and 6.80%. It was concluded that Phyllanthus emblica fruit nanoparticles (Phyllanthus emblica L.) could be formulated in capsule dosage forms with doses of 100 mg, 150 mg, and 200 mg; has antibacterial activity against Streptococcus mutans and Pseudomonas aeruginosa, and has no anti-inflammatory activity.